Does romantic partner support mitigate daily discrimination's association with mental health outcomes for diverse adults? - Gimarc, Caroline (Kansas State University, 2022)
Discrimination is ubiquitous across the United States. Discrimination has many negative consequences for mental health, including increased anxiety, depression, and stress. Racial and ethnic minorities may experience greater discrimination, which may put them at greater risk of negative mental health consequences. Theoretically grounded in the Double ABC-X Model and Critical Race Theory, and guided by existing literature, this study tested to what extent partner support and racial/ethnic identity may moderate the associations between discrimination and mental health (e.g., depression, anxiety, and stress). Participants were collected across the United States in a sample of 698 adults involved in a romantic relationship. Data were collected via surveys collected through the Prolific survey website. Greater discrimination was significantly linked with higher depression, anxiety, and stress. More partner support was significantly associated with lower depression, anxiety, and stress. Black participants reported significantly lower depression, anxiety, and stress; whereas Hispanic participants reported significantly higher levels of depression. In most cases, race and ethnicity did not moderate the association between discrimination and mental health outcomes, but Black participants increased at steeper rates in depression and anxiety as discrimination increased, relative to other groups. Partner support was found to be a moderator between discrimination and depression, where those experiencing high levels of discrimination in the context of high partner support reported significantly lower depression than those perceiving low partner supports. Implications of how discrimination is experienced are discussed.
Keywords: Discrimination; Mental health; Relationship; Support